Reviewing the Challenging Factors of Survival During COVID 19 Uncertainty - Tahreem Noor (Institute of Computer Science (IOCS), 2022)
Social media /online platforms are particularly important in times of crisis, as they are a vital channel for providing and ensuring access to information about products and services in an efficient manner. In a time of crisis and economic down turn, businesses usually begin to cut expenses, while they reduce their marketing budget; the key question is how business make an effort to be visible for their customers and how they react to uncertain situation. This research will review the existing literature to lays out the theoretical foundations to extract the ‘happenings’ and issues of marketing during the crises and provide some evidence of the global companies. It would suggest how businesses can better prepare themselves so that they can be more resilient to overcome the uncertainty and more agile to cope with these challenges in future. Despite the perennial need to understand and manage uncertainty in business, there is lack of data that highlight on the corporate marketing communication approaches for their customers. The findings of this research suggested that, during any crisis or high uncertainty, businesses must prepare themselves to alter their corporate marketing communication approaches and strategies, for their customers. This will reduce stereotype attitude, confusion, backlash or any negative connotation. To stay afloat in a highly competitive digital world, businesses can focus on clarity and tone of the communication message, align their operational and strategic process and it outcomes. Be vigilant by identifying the vulnerability and refocusing on brand values. Gather intelligent information using analytical tools – internal and external information. Devise appropriate reactive and proactive responsive strategies to survive in uncertain situation.